Perancangan dan Penerapan Websıte Rebrandıng Destınası Wısata Kota Batam Pada Oma Tour & Travel - Hendi Sama; Kevin Kevin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The purpose of this practical work is to help OMA Tour & Travel in promoting several tourist destinations in Batam City to potential customers by using the website as a promotional medium. This website contains a collection of information about tourist attractions such as place descriptions, available facilities, entrance ticket prices, operational times, as well as addresses and locations of tourist attractions. In the design process, the author will use Wordpress as a platform to design the website. Data collection methods used in this activity are observation and interviews. The result of the implementation is a website that is implemented through hosting services in the hope of increasing sales, as well as expanding the marketing reach of OMA Tour & Travel